Factors associated with retention of community health workers in maternal, newborn and child health programme in Simiyu Region, Tanzania - David P. Ngilangwa; George S. Mgomella (AOSIS, 2018)
Background: Attrition of community health workers (CHWs) continues to threaten the full realisation and sustainability of community-based health programmes globally.   Aim: This study aimed to understand factors associated with CHWs' recruitment and their retention.   Setting: This study was conducted in five districts of the Simiyu Region, namely, Bariadi, Busega, Itilima, Maswa and Meatu in north-western Tanzania.   Methods: In this cross-sectional study design, 341 CHWs who were working with the maternal health programme were randomly selected. Semi-structured questionnaires were administered to all participants. Data were descriptively and inferentially analysed using SPSS version 20.   Results: Majority (58.0%) of CHWs were below 35 years. Over half (53.1%) had completed primary education only. Motivation factors for being CHW were aspiration to serve the community and desire for further training to become a qualified medical practitioner. Community recognition and financial incentives were among the key retention reasons for the CHWs. Being married (odds ratio [OR] 5.9, 95% confidence interval [CI] 1.7-20.1) having prior volunteer experience (OR 10.5 95% CI 12.7-40.5) and prior employment OR 21.8 (CI 12.2-38.9) were positively associated with retention of CHWs, while being a female was negatively associated with retention OR 0.4 (CI 0.2-0.8).   Conclusions: Both financial and non-financial incentives were critical in contributing to the retention of CHWs. Thus, health programmes should carefully select CHWs by understanding their motives beforehand, and provide them with incentives.